AKIBAT HUKUM PENERBITAN SURAT IZIN USAHA PERTAMBANGAN (IUP) PADA KEKAYAAN ALAM KEPULAUAN SANGIHE - Zen Lutfulloh; Wahyu Donri (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2021)
Mining is a strategic sector that must be utilized by the government as well as possible. In accordance with the mandate contained in Article 33 of the 1945 Constitution, the government or the state is obliged to serve every citizen and resident to fulfill their basic needs in the context of public services and improving the welfare of the community. One of the public services that get a bad impression in the community is related to licensing services. At the beginning of 2021, there was a case phenomenon that became a polemic of debate among the community, government and environmental health observers. The phenomenon is that it is easy for the government to issue a mining business permit (IUP) decree to PT Tambang Mas Sangihe (TMS) which substantially violates Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands as well as having a large potential to cause environmental damage because some of the the area that gets the mining permit is a protected forest which is home to several endemic animals and plants that are threatened with extinction. This study uses normative research methods to determine the legal consequences of the policy. The purpose of this study is to provide several points of consideration to the government in terms of re-evaluating the decree. The results of this study indicate that Decree Number 163.K/MB.04/DJB/2021 has legal consequences for re-evaluation because in addition to violating other laws, the decision has the potential to cause damage to the natural environment in the Sangihe Islands. Key Words: Mining, Licensing, Environment